HOW EFFECTIVE COMMUNICATION IMPROVES EMPLOYEES’ ATTITUDE AND ORGANIZATIONAL PERFORMANCE? - Nurbarirah Ahmad; Muhammad Airil bin Ahmad; Muhammad Hazbullah bin Zulfakar; Nadia Izzaty binti Aliyashak; Jasrine Natasha binti Isham; Nur Amylia binti Iazhar (International Journal of Accounting, Finance and Business, 2022)
The objective of this study is to look at the effectiveness of communication among employees that influence organizational performance. The current study involves a reviewed research articles which were gathered from Emerald Insight and Hein Online databases. A total of 15 articles have been reviewed from the year 2017 to 2022. This study has been classified into the definitions and dimensions of effective communication and employee attitude and job performance. It was discovered that one way to improve job performance and employee attitude in the workplace is through effective communication. Furthermore, this study also explores the impact on creating an employee with a positive attitude at work. This study also emphasizes the prudent attitude of employees in carrying out daily tasks in a workplace to avoid the occurrence of problems in the workplace. It is importance to all employees to always communicate more effectively to maintain the strategy of humanitarian value in organizations using their communication proper channels properly. In addition, this study can also provide awareness to employees inorder to improve their communication skill at their workplace. This review study on effective communication and employee attitudes, and job performance will be benefit to the employees, managers and organization in providing a clear guideline in improving organizational performance.